IMPLIKASI STRATEGI PEMASARAN MELALUI KOMODIFIKASI AGAMA - HERLINA YUSTATI (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2017)
Religion in Indonesia is divided into Muslim, Christian, Catholic, Hindu, Buddhist,Khong Hu Chu and Other Religions. Religion Islam is the majority religion embracedby the Indonesian population, so that business people use this opportunity to recommodificationof religion. Commodification describes how capitalism launched anaim to accumulate capital, or realize the transformation of use-value into exchangevalue. The commodification of Islam in Indonesia occurred in various aspects. Mislanyacommodification